2019
DOI: 10.18280/ijht.370309
|View full text |Cite
|
Sign up to set email alerts
|

Radial Flow Field of Circular Bipolar Plate for Proton Exchange Membrane Fuel Cells

Abstract: The channel structure of flow field is an important influencing factor of the operation and performance of proton exchange membrane fuel cell (PEMFC). Based on circular bipolar plate, three radial flow fields, namely, Radial-I, Radial-II and Radial-III, with different structures were created, and compared to disclose the effects of radial channel on the flow field for the PEMFC. The results show that radial flow fields clearly outperformed traditional flow fields like parallel, single serpentine and multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Zhu et al [31] measured the relevant data between voltage and current density of a 5-serpentine flow field PEMFC with professional equipment and plotted their polarization curves, where the voltage was set between 0.2 and 0.9 V. To verify the rationality of the simulation results, the same channel structure as Zhu was established and simulated. Visible able to be seen from the polarization curve shown in Fig.…”
Section: Validation Of Model Rationalitymentioning
confidence: 99%
“…Zhu et al [31] measured the relevant data between voltage and current density of a 5-serpentine flow field PEMFC with professional equipment and plotted their polarization curves, where the voltage was set between 0.2 and 0.9 V. To verify the rationality of the simulation results, the same channel structure as Zhu was established and simulated. Visible able to be seen from the polarization curve shown in Fig.…”
Section: Validation Of Model Rationalitymentioning
confidence: 99%
“…Though the relation between the power generation characteristics and O2 profile or flow filed distribution was discussed, that between the power generation characteristics and the temperature distribution was not studied. Regarding the general PEMFC operated below 353 K, the several flow fields of separator such as a modified parallel flow field [16], a blocked flow field [17], a modified serpentine wave flow filed [18], a straight channel with baffled obstacles [19] and an ultrathin steel separator whose thickness was 0.1 mm [20] were investigated. Since the weight ratio of separator to that of total cell is approximately 80 % [21], it is important to optimize the design of separator.…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered that the effect of the channel depth on cell performance compared to other parameters was not important. It was concluded that the radial gas flow field was more functional for maximum cell performance than parallel and serpentine flow field patterns [18].…”
Section: Introductionmentioning
confidence: 99%